2019
DOI: 10.1136/rapm-2018-100104
|View full text |Cite
|
Sign up to set email alerts
|

An Obturator Nerve Block does not Alleviate Postoperative Pain after Total Hip Arthroplasty: a Randomized Clinical Trial

Abstract: Background and objectivesA substantial group of patients suffer from moderate to severe pain following elective total hip arthroplasty (THA). Due to the complex innervation of the hip, peripheral nerve block techniques can be challenging and are not widely used. Since the obturator nerve innervates both the anteromedial part of the joint capsule as well as intra-articular nociceptors, we hypothesized that an obturator nerve block (ONB) would decrease the opioid consumption after THA.MethodsSixty-two patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…There was no difference in the resting VAS between the two groups, and our explanations for this follow. 1) The obturator nerve plays a limited role at rest, with a study showing that the block of the obturator nerve did not relieve pain after total hip arthroplasty [23]; this suggests that the obturator nerve was less important than the femoral nerve in analgesia during hip fractures. 2) There might be errors in the assessment of the obturator nerve block, as accurate assessments have proven quite difficult due to significant variation in the cutaneous distribution of the obturator nerve.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in the resting VAS between the two groups, and our explanations for this follow. 1) The obturator nerve plays a limited role at rest, with a study showing that the block of the obturator nerve did not relieve pain after total hip arthroplasty [23]; this suggests that the obturator nerve was less important than the femoral nerve in analgesia during hip fractures. 2) There might be errors in the assessment of the obturator nerve block, as accurate assessments have proven quite difficult due to significant variation in the cutaneous distribution of the obturator nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of the SFIB with ON block, on the other hand, is still debatable. In some previous studies, the ON block did not reduce pain after hip arthroplasty (Nielsen et al, 2019). At present, Zheng et al (2021) improved the USG-SFIB technique of analgesic for total hip arthroplasty.…”
Section: Discussionmentioning
confidence: 68%
“…Study II revealed that an ONB had no effect on post‐operative pain after THA; subjects with an ONB had an opioid consumption of (mean [SD]) 39.9 [22.3] mg opioids (oral morphine equivalents) during the first 12 post‐operative hours. The corresponding dose in controls was 40.5 [30.5] mg ( P = .93) . In Study III, we found that an IPB did not induce muscle weakness in volunteers.…”
mentioning
confidence: 69%